Self-confidence and its relationship to completing the 100-meter freestyle race - Matrood, Maysaa (Journal of Physical Education, 2024)
This study explored the relationship between self-confidence and the achievement of running the 100-meter freestyle among fourth-year female students at the College of Physical Education and Sports Sciences at the University of Baghdad, using the descriptive approach. A purposive sample of 20 female students was selected, and data was collected using the self-confidence scale (Allawi, 1998) and the 100-meter freestyle running test. The results showed a strong significant correlation between self-confidence and the 100-meter freestyle running test (r = 0.892, Sig = 0.000). This result supports the hypothesis that self-confidence plays a crucial role in achieving athletic achievement. I concluded that the study supports the importance of self-confidence in improving athletic performance. Some recommendations were reached, the most important of which is conducting similar studies at other educational levels, using the self-confidence measure in other activities, and conducting Similar studies on males. This study contributes to enhancing scientific understanding of the relationship between self-confidence and athletic achievement